Latissimus Dorsi Tendon Transfer using Tendinous Allograft for Irreparable Rotator Cuff Lesions: Surgical Technique - Miyazaki, Alberto Naoki (Sociedade Brasileira de Ortopedia e Traumatologia. Published by Thieme Revnter Publicações Ltda, 2019)

(untitled) (Rev Bras Ortop (Sao Paulo))
Latissimus dorsi transfer around the shoulder is the most frequently used surgical technique to treat young patients with irreparable posterosuperior rotator cuff lesions. This technique, as initially described and popularized by Gerber et al., has two main drawbacks that may predispose to complications and unsatisfactory functional results: 1) postoperative rupture of the origin of the deltoid, as its detachment from the acromion is necessary during the superior approach to the shoulder; and 2) postoperative rupture of the transferred tendon. In an attempt to avoid these problems, the authors have developed the following modifications to the original technique. Through a deltopectoral approach, the latissimus dorsi tendon is identified and detached from the humerus shaft. After being reinforced and elongated with a tendinous allograft, it is transferred around the humerus and fixed to the superolateral aspect of the greater tubercle. No rigid thoraco-brachial immobilization is used postoperatively.